In vitro appraisal of antibacterial activity of Entada spiralis’s leaves extracts against phytopathogenic bacteria Erwinia chrysanthemi and Erwinia carotovora - Salim, Khairil Syazwan; Harun, Aiza; Abdul Aziz, Noorshilawati; Daud, Shaari; Ahmat, Norizan; Mat So'Ad, Siti Zaiton; Taib, Mariam; Adzahar, Noor Suhana (AIP Publishing, 2024)
Entada spiralis Ridl. or also known as ‘akar beluru’ or ‘akar sintok’, is one of the least studied species in the Fabaceae family. The species was famous for its soap-like properties in which the natives use them as soap and shampoo for hygiene and treating itchiness. The phytochemicals and biochemicals properties of this plant have always been an interesting area to be discovered, as the study of the species is still scanty. In this study, the aim is to evaluate the antibacterial effects of the E. spiralis leaves extracts against two Gram-negative phytobacteria species, Erwinia chrysanthemi (ATCC 437624) and Erwinia carotovora (ATCC 15713) for the discovery of the natural active bactericides. Hexane, dichloromethane, ethyl acetate and methanol were used as menstruum in producing the extracts through cold maceration method. The extracts were subjected to screening tests for identification of phytochemicals which revealed the presence of phenolics, terpenoids, saponins, coumarins, flavonoids, and tannins. Antibacterial activities of the extracts were assessed via Kirby-Bauer disk diffusion method by measuring the inhibition zones post-incubation for 24 hours at room temperature. While, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated through broth microdilution method after incubation at room temperature for 24 hours. Output data from this study showed that, methanol extract against E. chrysanthemi and ethyl acetate extract against E. carotovora have the maximum zone of inhibition in antibacterial susceptibility with 22.7 ± 0.6 mm and 26.3 ± 0.6 mm respectively at 400 mg/mL concentration. In accordance with MIC, E. chrysanthemi was revealed to be most susceptible in methanol extract with MIC value of 1.56 ± 0.00 mg/mL (MBC value at 3.13 ± 0.00 mg/mL). E. carotovora has been determined to be best susceptible also in ethyl acetate extracts with MIC values of 0.65 ± 0.23 mg/mL (MBC value at 2.60 ± 0.90 mg/mL).